Search for anomalous couplings of Higgs bosons using events with electrons/muons and tau leptons in proton-proton collisions at √s = 13 TeV at the Large Hadron Collider - Mitchell, Tyler (Kansas State University, 2021)
A study of the Higgs boson coupling to gauge bosons is presented using the τ[subscript]eτ[subscript]h and τ[subscript]μτ[subcript]h decay channels. The effects of CP-violation and anomalous couplings in Higgs gluon- gluon fusion and vector boson fusion production mechanisms are analyzed using machine learning and matrix element techniques. These techniques take advantage of the correlations present between jets produced in association with the Higgs boson to produce the most sensitive analysis to date. The analysis is conducted using data collected by the CMS experiment at 13 TeV center-of-mass energy corresponding to an integrated luminosity of 139 fb⁻¹.
Keywords: Higgs boson; High energy physics; Coupling; Compact Muon Solenoid (CMS)